Kesepadanan Tekstual Konstruksi Tema Rema dalam Takarir Bahasa Arab Film Mitos Nyawur: Studi Kasus Penerjemahan Purbalingga / Textual Equivalence of Theme and Rheme in the Arabic Subtitle of Nyawur Mith Movie: Case Study in Purbalingga – Arabic Translatio - Muhammad Yunus Anis (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2022)
This study will examine the textual equivalence of the construction of Theme and Rheme in the subtitle of the film “Nyawur”, Purbalingga Myth, (Purbalingga (L1) – Arabic (L2)). The data in this study were taken from the subtitle of the short film Myth “Nyawur” (sowing salt in the hope that the rain would stop) in VIU. Films related to these myths use subtitles in Arabic. Some of these films use local languages ​​that contain mythical terms. The formulation of the first problem in this study is how the textual equivalence of the translation of Themes and Rheme in the short films screened in VIU. Meanwhile, the second problem is how the strategy is used in translating the construction of Themes and Rhemes in the short film. This study uses a qualitative descriptive method using three main stages, namely: (1) data collection using the observation method, in this case the units of language are one of the core studies to see the textual equivalence in the local language with Arabic subtitles, (2) data analysis using the equivalence method to see and measure the lexical equivalence of the construction of Themes and Rhemes between the source language and the target language, along with what strategies are used in translating the myth. The final stage (3) reports the results by describing the textual equivalence of the construction of Themes and Rhemes in the source language and the target language. This study concludes that the translation of subtitles tends to be in the target language (reader oriented). This research is expected to have an impact in the study of Arabic translation, in particular improving the quality of translation of Arabic subtitles in local films in Indonesia so that they can be enjoyed by Arabic speakers. مستلخص ستدرس هذه الدراسة التكافؤ النصي لبناءTheme and Rheme في العنوان الفرعي لفيلم “Nyawur